Translation of Old Polish Criminal Law Terminology into English and Korean in Adam Mickiewicz’s Epic Poem “Master Thaddeus, or the Last Foray in Lithuania: A Nobility’s Tale of the Years 1811–1812, in Twelve Books of Verse” - Matulewska, Aleksandra (Springer, 2023)
CC-BY